Вплив параметрів інтеграторів на нелінійність функції перетворення сигма-дельта модулятора високого порядку - Кочан, Р.В. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
There is developed the simulation model of single-bit high order sigma- delta modulator. Also using this model there are investigated influence of integrator’s nonlinearity on modulator’s nonlinearity for second and third order sigma-delta modulators. There is identified integrator’s decreasing coefficient by sigma-delta modulator of second and third order.